Serum CA125, CA199, estradiol, FSH, IL-6, TNF-a in endometriosis after administration of Tripterygium wilfordii glycosides - Xu Fangdan; Xu Ying; Qiu Jianping (Journal of Medical Biochemistry, 2025)
Background: To evaluate the therapeutic effects of Tripterygium wilfordii glycosides on endometriosis (EMs) and their effects on serum sex hormone levels, tumour markers, and inflammatory factors (serum CA125, CA199, Estradiol, FSH, IL-6, TNF-a). Methods: A total of 108 patients were randomly divided into control, progesterone, and Tripterygium wilfordii glycoside-treated groups, each receiving treatment for three months. The clinical efficacy and serum levels of estradiol, follicle-stimulating hormone, tumour markers (cancer antigen125 and cancer antigen199), and pro-inflammatory cytokines were compared before and after treatment. Results: The Tripterygium wilfordii glycoside group exhibited a significantly higher clinically effective rate (90.74% versus 75.93%) and more significant reductions in estradiol, follicle-stimulating hormone, cancer antigen125, cancer antigen199, IL-6, TNF-a, and HSCRP levels than the control group. Conclusions: Tripterygium glycosides exhibit significant clinical efficacy in treating patients with EMS by significantly improving serum sex hormone levels, reducing tumour marker levels, alleviating inflammatory reactions, and exerting minimal toxic side effects.